The Effectiveness of Sport Animations in Children's Sport Behavior (Case Study: The Animation of FOOTBALISTHA) - Mostafa Moghadas; Farzam Farzan (رشد و یادگیری حرکتی ورزشی, 2017)
The aim of this study was to evaluate the effectiveness of "FOOTBALISTHA" animation to attract children to football. Animation, as a tool for multimedia education, can show longitudinal changes of events such as move, process and procedures and it can affect children’s absorption. The population of the study consisted of all male primary school students (fourth to sixth grade) in Amol city (N=15000). 500 students were selected by cluster random sampling method. A researcher-made questionnaire was used for data collection. The face validity was confirmed by professors and construct validity and reliability (0.91) were assessed as suitable. Descriptive statistics, confirmatory factor analysis, Kolmogorov-Smirnov, binominal and Friedman tests were used with SPSS22 and Amos18. The findings showed that "FOOTBALISTHA" animation was effective in children’ attention to football, their interest in football and their tendency to football and finally playing football. So "FOOTBALISTHA" animation had sufficient effectiveness in changing children's sport behavior and the findings of this study were consistent with AIDA model.